Perancangan Gedung Rental Office Dengan Konsep Efesiensi Energi - Clara Chabelita; Hamidah, Noor (JURNAL PERSPEKTIF ARSITEKTUR, 2024)
Indonesia currently has the status of a developing country, so it is increasing the construction of high-rise building infrastructure as a solution to limited space in urban areas. One of the buildings that is being intensively built in this country is rental office buildings where the need for these buildings increases along with Indonesia's economic growth. On the other hand, the green architecture or green building movement with the aim of creating environmentally friendly buildings is starting to emerge in Indonesia as an act of resistance to the issue of global warming in the world. Responding to this issue, Architectural Design V's task this time was to design a high-rise rental office building in Palangka Raya City, Central Kalimantan Province with a green building concept that focuses on energy efficiency.